Influence of the Wave Form on the Material Response Delay - J. R. Azinheira; L. Reis; A. M. R. Ribeiro (Shock and Vibration)
To model damping effects in structural dynamics, the literature provides a wide range of alternatives. The different models claim different advantages and fields of use where they are useful but, in the end, the compliance of the model with the experimental results, within a given tolerance, is the ultimate criterion for assessing its quality. In the present paper, the behaviour of a simple steel specimen is studied, taking as a focus the time response of the material. Since the harmonic response is well established, the authors propose to submit the specimen to a trapezoidal periodic load and study the behaviour of the response to the load changes. A simple setup was used, using a steel specimen loaded in the linear regime. A carefull test procedure was carried out in order to characterize the dissipation in a quasi-static periodic load. The experimental results show that the response delay to a ramp load depends on the durations of both the previous flat and the ramp itself.